Oxford illustrated encyclopedia of the universe - Roy, Archie (New York : Oxford, 1992)
Containing over 1100 alphabetically arranged entries, this major reference work ranges in subject matter from the evolution of the stars to the technological instruments used to observe them.
Keywords: Astronomy -- Encyclopedias; Astronomy